Composite material and preparation method thereof, light-emitting device and display device
By compounding nickel oxide with PEDOT: PSS and connecting organic base groups on its surface, the stability of PEDOT: PSS under optical and thermal conditions has improved the stability of the composite materials and the injecting performance of the acupuncture, which enhances glowing The performance and stability of the device.
Patent Information
- Application Number
- CN202310935493.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-01-28
AI Technical Summary
PEDOT: PSS, as an organic material, has poor stability under photothermal conditions, which affects its application.
By compounding nickel oxide with PEDOT: PSS, and connecting negative organic groups with negative electromegia on its surface, a composite material is formed to improve its stability and acupoint injection performance.
Improve the stability of the composite materials and the injecting performance of the acupoints, and enhance the performance and stability of the luminous device.
Smart Images

Figure CN119371783A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a composite material and a preparation method thereof, a light-emitting device and a display apparatus. Background Art
[0002] Conductive polymer PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid)) usually exists in the form of aqueous solution and has the characteristics of high conductivity and adjustable conductivity. This conductive polymer material is composed of two substances, PEDOT and PSS, where PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer) and PSS is polystyrene sulfonate. The solubility of PEDOT can be greatly improved by the access of PSS. At present, PEDOT:PSS has been used in transparent conductive electrodes (OTFT, film / touch switches, etc.), antistatic films, and hole transport layers in optoelectronic devices such as organic light-emitting diodes and solar cells.
[0003] However, as an organic material, PEDOT:PSS has poor stability under photothermal conditions, which affects its application. Summary of the invention
[0004] In view of this, the present application provides a composite material and a preparation method thereof, a light-emitting device and a display device, aiming to provide a composite material that has good injection performance and good stability.
[0005] The embodiment of the present application is implemented as follows. In a first aspect, a composite material is provided, comprising poly(3,4-ethylenedioxythiophene): poly(styrenesulfonic acid) and nickel oxide, wherein the surface of the nickel oxide is connected with a negatively charged organic group, wherein the organic group has one or more of the following structures:
[0006]
[0007] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of -H, -D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen.
[0008] In a second aspect, the present invention also provides a method for preparing a composite material, comprising:
[0009] Providing a first mixture, wherein the first mixture includes poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) and a first solvent, wherein the first solvent contains a hole sacrificial agent;
[0010] After the first mixture is subjected to a first light treatment, an organic nickel salt is added to the first mixture, and the mixture is subjected to a second light treatment to obtain a composite material;
[0011] Wherein, the organic nickel salt comprises an organic anion and a nickel ion, and the organic anion comprises one or more of the following structural formulas:
[0012]
[0013] Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of -H, -D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen.
[0014] In a third aspect, an embodiment of the present application further provides a light-emitting device, comprising: a first electrode and a second electrode arranged opposite to each other; a light-emitting layer arranged between the first electrode and the second electrode; a hole functional layer arranged between the first electrode and the light-emitting layer; wherein the material of the hole functional layer includes the above-mentioned composite material, or includes a composite material obtained by the preparation method of the above-mentioned composite material.
[0015] In a fourth aspect, an embodiment of the present application further provides a display device, comprising the light-emitting device as described above.
[0016] The composite material of the present application, a composite of an organic conductive polymer PEDOT:PSS and an inorganic material nickel oxide, improves the stability of the composite material. The organic groups connected to the surface of the nickel oxide can increase the hole concentration of the composite material, effectively promote the hole injection performance and improve the film-forming property of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a composite material provided in the present application;
[0019] Figure 2 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application.
[0020] Figure 3 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;
[0021] Figure 4 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;
[0022] Figure 5 and Figure 6 AFM images of the hole functional layer in device comparative example 1 and device embodiment 2 respectively;
[0023] Figure 7 EQE-J curves of device examples 1-9 and device comparative examples 1-2;
[0024] Figure 8 EQE-storage time diagram of device embodiments 3 and 7 and device comparative examples 1 and 2;
[0025] Fig. 9 JV curves of single hole devices of device embodiments 1-9 and comparative examples 1-2;
[0026] Fig.10 This is the valence band position diagram of nickel oxide.
[0027] Reference numerals: light emitting device 100 ; first electrode 10 ; second electrode 20 ; light emitting layer 30 ; hole functional layer 40 ; electron functional layer 50 , electron injection layer 51 , electron transport layer 52 . DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.
[0029] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0030] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0031] In the present application, "ring atoms" means the number of atoms of the ring atoms constituting the ring itself in a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) formed by atoms bonding to form a ring, i.e., the number of atoms forming the ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The same is true for the "ring atoms" described below, unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5.
[0032] In the present application, "aryl or aromatic group" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "aryl having 5 to 30 ring atoms" refers to an aromatic group containing 5 to 30 ring atoms, and the aromatic group can be optionally further substituted. Preferably, substituted or unsubstituted aromatic groups having 6 to 24 ring atoms are used, more preferably substituted or unsubstituted aromatic groups having 6 to 18 ring atoms are used, and particularly preferably substituted or unsubstituted aromatic groups having 6 to 14 ring atoms are used, and the aromatic group can be optionally further substituted; suitable examples include, but are not limited to, phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, fluoranthenyl, triphenylene, pyrenyl, perylene, naphthyl, fluorenyl, dinaphthylenyl, acenaphthene and derivatives thereof. It is understandable that multiple aromatic groups may also be interrupted by short non-aromatic units (e.g. <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, diaryl ether systems should also be included in the definition of aromatic groups.
[0033] In the present application, "heteroaryl or heteroaromatic group" means that at least one carbon atom is replaced by a non-carbon atom on the basis of an aromatic group, and the non-carbon atom can be an N atom, an O atom, an S atom, an Si atom, a P atom, etc. For example, "heteroaryl having 5-30 ring atoms" means a heteroaryl having 5 to 30 ring atoms, preferably a substituted or unsubstituted heteroaryl having 5 to 24 ring atoms, more preferably a substituted or unsubstituted heteroaryl having 5 to 18 ring atoms, and particularly preferably a substituted or unsubstituted heteroaryl having 5 to 14 ring atoms, and the heteroaryl is optionally further substituted; suitable examples include, but are not limited to: thienyl, furanyl, pyrrolyl, oxadiazolyl, triazolyl, imidazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, Acridinyl, pyridazinyl, pyrazinyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, benzothienyl, benzofuranyl, indolyl, pyrroloimidazolyl, pyrrolopyrrolyl, thienopyrrolyl, thienothiphenyl, furopyrrolyl, furofuranyl, thienofuranyl, benzisoxazolyl, benzisothiazolyl, benzimidazolyl, o-naphthyl, phenanthridinyl, primary pyridyl, quinazolinone, dibenzothienyl, dibenzofuranyl, carbazolyl and derivatives thereof.
[0034] In the present application, "*" indicates a connection site or a fusion site. When the connection site is not specified in the group, it means that an optional connection site in the group is used as the connection site. When the fusion site is not specified in the group, it means that an optional fusion site in the group is used as the fusion site.
[0035] In the present application, a single bond or a bond at a connection point connecting a substituent runs through the corresponding ring, indicating that the substituent can be connected to an optional position of the ring or the connection point can be an optional position of the ring. This means that the attachment site can be any site on the loop.
[0036] The present application provides a composite material, comprising poly(3,4-ethylenedioxythiophene): poly(styrene sulfonic acid) and a p-type metal oxide, wherein the p-type metal oxide is selected from nickel oxide, and a negatively charged organic group is connected to the surface of the nickel oxide, and the organic group has one or more of the following structures:
[0037]
[0038] Wherein, each occurrence of R1, R2, R3, and RR4 is independently selected from one or more of -H, -D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
[0039] Wherein, X is a halogen, selected from one or more of F, Cl, Br, and I.
[0040] It can be understood that the aromatic group having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl specifically means that the H on the aromatic group having 5-30 ring atoms can be replaced by one or more of hydroxyl, -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
[0041] Optionally, the number of carbon atoms in the alkyl, aryl or heteroaryl group in the C1-C30 alkyl group, the aryl group having 5-30 ring atoms, and the heteroaryl group having 5-30 ring atoms can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.
[0042] Further, in one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 5-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
[0043] Further, each occurrence of R1, R2, R3, and R4 is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, benzopyridyl, pyrimidyl, benzopyrimidyl, amino, and one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, amino substituted with at least one of -OH, -X, methyl, ethyl, n-propyl, isopropyl, n-butyl, and amino; X is halogen selected from one or more of F, Cl, Br, and I.
[0044] In one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, phenyl, naphthyl, biphenyl, pyridyl, benzopyridyl, pyrimidyl, benzopyrimidyl, amine, or one or more of the following structural formulas:
[0045]
[0046] In one embodiment, each occurrence of R1, R2, R3, and R4 is independently selected from methyl, phenyl, amino,
[0047]
[0048] Among them, the amine group is -NH2.
[0049] Furthermore, the organic group may include one or more of the following structural formulas:
[0050]
[0051] It is understood that the enol form can exist in the keto form, i.e. Can also
[0052] In this embodiment, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid), namely PEDOT:PSS, is an organic conductive polymer. The stability of the composite material is improved by compounding the organic material with the inorganic material (nickel oxide). The surface of the nickel oxide is connected with organic groups, which can increase the hole concentration of the composite material and effectively promote the hole injection performance. On the other hand, the organic groups are coordinated and connected to the surface of the nickel oxide, and can combine with a large number of oxygen defects on the surface of the nickel oxide, thereby reducing the surface defects of the nickel oxide, increasing the dispersibility of the nickel oxide, and improving the film-forming property of the composite material.
[0053] In one embodiment, the average particle size of the nickel oxide is 3-10 nm, specifically 3-8 nm, 4-8 nm, 4-6 nm, 5-6 nm, etc.
[0054] In one embodiment, the mass ratio of the nickel oxide to the PEDOT:PSS is 30-50%, specifically 30-45%, 35-45%, 35-40%, 30-35%, 45-50%, etc. The mass ratio of the nickel oxide to the PEDOT:PSS can improve the stability and hole injection performance of the composite material.
[0055] In one embodiment, in PEDOT:PSS, the mass ratio of PEDOT to PSS may be 5:8 to 1:20, specifically 5:8 to 1:10, 1:5 to 1:10, 1:5 to 1:8, etc.
[0056] The present application also provides a method for preparing a composite material, see Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for preparing a composite material provided by the present application, which specifically includes the following steps:
[0057] Step S11: providing a first mixture, wherein the first mixture includes PEDOT:PSS and a first solvent;
[0058] Step S12: After the first mixture is subjected to the first light irradiation treatment, an organic nickel salt is added to the first mixture, and the mixture is subjected to the second light irradiation treatment to obtain a composite material.
[0059] In this embodiment, the first mixture is subjected to a first light irradiation treatment, and the organic hole transport material can excite electrons (e - ), the electrons can react with the oxygen and water in the first mixture system to generate hydroxide, and after the organic nickel salt is added to the system, the nickel ions in the organic nickel salt can react with the hydroxide to generate nickel oxide, and the second light treatment can be continued to promote the generation of electrons and improve the efficiency of the photocatalytic reaction. The method of this embodiment can generate nickel oxide in situ. The reaction mechanism can be referred to as follows:
[0060]
[0061] O2+2H2O+4e - →4OH -
[0062] Ni 2+ +OH - →NiOx+H2O;
[0063] Here, NiOx is nickel oxide.
[0064] In this embodiment, the nickel ions in the organic nickel salt are photocatalyzed by PEDOT:PSS to generate nickel oxide in situ, thereby improving the binding property of PEDOT:PSS and nickel oxide. The organic anions in the organic nickel salt can be connected to the surface of the nickel oxide generated in situ, thereby reducing the defects of the nickel oxide, improving the hole injection performance of the composite material, and effectively preventing the regrowth and agglomeration of the nanoparticles of nickel oxide, thereby improving the uniformity and film-forming performance of the particles in the composite material.
[0065] In the step S11:
[0066] In the first mixture, the mass percentage concentration of PEDOT:PSS may be 0.1-20%, specifically 0.1-0.6%, 0.6-5%, 5-10%, 10-20%, etc.
[0067] The first solvent includes one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, toluene, and DMSO.
[0068] In one embodiment, the first solvent may be selected from water, that is, the first mixture may be a PEDOT:PSS aqueous solution. Specifically, the PEDOT:PSS aqueous solution (CAS No.: 155090-83-8) may be purchased commercially or prepared by methods known in the art.
[0069] Specifically, the mass percentage concentration of PEDOT:PSS in the PEDOT:PSS aqueous solution may be 0.6-5%, specifically 0.6-4.0%, 1.0-4.0%, 1.0-3.0%, 2.0-3.0%, 3.0-5.0%, etc.
[0070] In one embodiment, in PEDOT:PSS, the mass ratio of PEDOT to PSS may be 5:8 to 1:20, specifically 5:8 to 1:10, 1:5 to 1:10, 1:5 to 1:8, etc.
[0071] In one embodiment, the first mixture also includes a hole sacrificial agent, which can consume holes generated by photocatalysis, thereby providing more electrons to generate hydroxide. Further, the hole sacrificial agent can include one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, lactic acid, etc.
[0072] In one embodiment, the mass ratio of the hole sacrificial agent to the PEDOT:PSS may be (0.5-1.5):5, specifically (0.5-1.3):5, (0.8-1.3):5, (0.8-1.0):5, (0.5-0.8):5, (1.3-1.5):5, etc. The mass ratio can provide an excess of the hole sacrificial agent to consume the holes generated in the photocatalytic reaction, and also avoid the waste of the hole sacrificial agent.
[0073] In step S12:
[0074] An organic nickel salt is added to the first mixture, wherein the mass ratio of the organic nickel salt to the PEDOT:PSS is (2-3):5, i.e. (40-60):100, and specifically can be (10-50):100, (20-50):100, (20-40):100, (30-40):100, etc. The mass ratio can provide enough of the organic nickel salt to form nickel oxide, thereby generating a sufficient amount of nickel oxide in situ, forming an inorganic-organic composite material with better stability, and providing enough organic anions to coordinate and connect to the nickel oxide, thereby reducing the surface defects of the nickel oxide, improving the film-forming property of the composite material, increasing the hole concentration of the semiconductor, and effectively promoting the injection of holes in the device.
[0075] The organic anion and nickel ion included in the organic nickel salt. Further, the organic anion can be specifically referred to the relevant description of the organic group in the composite material, which will not be described in detail here.
[0076] In a specific embodiment, the organic nickel salt may specifically include: one or more of nickel (II) aminosulfonate, nickel (II) p-toluidine-2-sulfonate, nickel (II) trifluoromethanesulfonate, nickel (II) acetylacetonate, nickel (II) p-toluenesulfonate, and the like.
[0077] In one embodiment, the organic nickel salt is added to the first mixture in the form of a solution. Specifically, the second solvent corresponding to the organic nickel salt may include one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, toluene, and DMSO. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, and n-butanol. The ether solvent includes one or more of methyl ether and ethyl ether.
[0078] In one embodiment, the organic nickel salt is added while the first mixture is in a stirring state to improve the mixing uniformity of the first mixture and the organic nickel salt, thereby promoting the generation of nickel oxide.
[0079] In one embodiment, the duration of the first light treatment is 1 to 2 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, etc.
[0080] In one embodiment, the first illumination treatment is full-spectrum illumination treatment, that is, full-band illumination is used.
[0081] In one embodiment, the wavelength range of the first light treatment is 200-2500 nm, such as one or more of 200-380 nm, 380-760 nm, 760-2500 nm, etc.
[0082] In one embodiment, the first light treatment may include one or more of ultraviolet light band (UV for short, wavelength 200-380nm), visible light band (VL for short, wavelength 380-760nm) or infrared light band (IR for short, wavelength 760-2500nm).
[0083] In one embodiment, the light source for the first illumination treatment may be a single light source or a composite light source formed by multiple light sources.
[0084] In a specific embodiment, the light source of the first light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp can be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.
[0085] In one embodiment, during the first light irradiation process, the first mixture is in a stirring state to improve mixing uniformity, improve light irradiation uniformity, and improve heat dissipation.
[0086] In one embodiment, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30°C, such as 0-4°C, 4-20°C, 20-25°C, 25-30°C, etc. Specifically, the first mixture can be protected by circulating condensed water to control the temperature of the first mixture within a preset range to avoid excessive temperature of the first mixture due to heat generation from light.
[0087] The second light treatment time is 4 to 8 hours, specifically 5 to 8 hours, 5 to 7 hours, 6 to 7 hours, 7 to 8 hours, etc. The second light treatment within the time range can photocatalytically obtain the preset amount of nickel oxide.
[0088] In one embodiment, the second illumination treatment is full-spectrum illumination treatment, that is, full-band illumination is used.
[0089] In one embodiment, the wavelength range of the second light treatment is 200-2500 nm, such as one or more of 200-380 nm, 380-760 nm, 760-2500 nm, etc.
[0090] In one embodiment, the second light treatment may include one or more of ultraviolet light band (UV for short, wavelength 200-380nm), visible light band (VL for short, wavelength 380-760nm) or infrared light band (IR for short, wavelength 760-2500nm).
[0091] In one embodiment, the light source for the second illumination treatment may be a single light source or a composite light source formed by multiple light sources.
[0092] In a specific embodiment, the light source of the second light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp can be 200-500W, such as 200-300W, 300-400W, 400-500W, etc.
[0093] In one embodiment, an organic nickel salt is added to the first mixture to obtain a second mixture, and a second light treatment is continued. During the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0 to 30°C, such as 0 to 4°C, 4 to 20°C, 20 to 25°C, 25 to 30°C, etc. Specifically, the second mixture can be protected by circulating condensed water to control the temperature of the second mixture within a preset range to avoid excessive temperature of the second mixture due to heat generation from light.
[0094] In one embodiment, an organic nickel salt is added to the first mixture to obtain a second mixture, and during the second light irradiation treatment, the second mixture can be in a stirring state to improve mixing uniformity and increase the rate of generating nickel oxide.
[0095] In one embodiment, after the second light treatment, the method further includes: using a cleaning agent to perform sedimentation washing on the mixture N times, where N is an integer greater than or equal to 2, such as washing three times. The cleaning agent may include one or more of ethyl acetate and acetone. In this embodiment, unreacted reactants, such as unreacted organic nickel salts, may be removed by multiple washings.
[0096] The present application provides a light emitting device, referring to Figure 2 , Figure 2 The present application provides a structural schematic diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 that are relatively arranged, and a light-emitting layer 30 that is arranged between the first electrode 10 and the second electrode 20, and a hole functional layer 40 that is arranged between the first electrode 10 and the light-emitting layer 30.
[0097] The material of the hole functional layer 40 includes the composite material provided in the present application, or includes the composite material prepared by the preparation method of the composite material provided in the present application.
[0098] In this embodiment, the material of the hole functional layer 40 includes a composite material, namely, PEDOT:PSS and nickel oxide. The composite material and the inorganic material are combined to improve the stability of the composite material and the hole functional layer 40, so that the hole functional layer 40 has good hole transport performance and good hole injection performance. The surface of the nickel oxide is connected with a negatively charged organic group, and the organic group is coordinated and connected to the surface of the nickel oxide. On the one hand, it can increase the hole concentration of the composite material and effectively promote the injection of holes in the hole functional layer 40; on the other hand, the organic group is coordinated and connected to the surface of the nickel oxide, which can combine with a large number of oxygen defects on the surface of the nickel oxide, reduce the surface defects of the nickel oxide, increase the dispersibility of the nickel oxide, and improve the film forming property of the composite material, thereby improving the uniformity and density of the film layer of the hole functional layer 40, reducing and avoiding the leakage current phenomenon of the light-emitting device 100, improving the stability of the light-emitting device 100, and reducing the interface barrier between the hole functional layer 40 and the adjacent film layer, thereby further improving the hole injection.
[0099] In one embodiment, the material of the hole functional layer 40 is composed of the composite material. Further, the hole functional layer 40 is a single-layer film structure. In this embodiment, the composite material is used as the material of the hole functional layer 40, and the performance of hole injection and hole transport can be achieved through the single-layer hole functional layer 40.
[0100] In other embodiments, the material of the hole functional layer 40 may include other materials such as metal elements in addition to the composite material.
[0101] In one embodiment, the thickness of the hole functional layer is 15-40 nm, specifically 15-35 nm, 20-35 nm, 20-30 nm, 25-30 nm, 15-20 nm, 35-40 nm, etc.
[0102] In one embodiment, the material of the light-emitting layer 30 is selected from organic light-emitting materials or quantum dot light-emitting materials.
[0103] The organic light-emitting material may be selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light;
[0104] The quantum dot luminescent material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdS At least one of dZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, Sn At least one of PbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb , GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;
[0105] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.
[0106] In one embodiment, the quantum dot luminescent material includes one or more of red quantum dots, green quantum dots, and blue quantum dots.
[0107] The thickness of the light emitting layer 30 may be 5 to 100 nm, specifically 5 to 15 nm, 15 to 30 nm, 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, 30 to 50 nm, 50 to 100 nm, etc.
[0108] In a specific embodiment, the quantum dots are selected from oily quantum dots, and the surface of the quantum dots is connected with a ligand that is easily soluble in a solvent with low polarity, including at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. As a specific embodiment, the acid ligand is at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand is at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octadecylamine; the (oxygen) phosphine ligand is at least one of trioctylphosphine and trioctylphosphine oxide.
[0109] In one embodiment, the light emitting device 100 may further include an electronic functional layer 50 , wherein the electronic functional layer 50 is disposed between the second electrode 20 and the light emitting layer 30 .
[0110] In one embodiment, the electronic functional layer 50 may include one or both of an electron injection layer 51 and / or an electron transport layer 52; when the electronic functional layer 50 includes two layers, the electron injection layer 51 and the electron transport layer 52, the electron injection layer 51 is arranged close to the second electrode 20 side, and the electron transport layer 52 is arranged close to the light-emitting layer 30 side.
[0111] In one embodiment, the material of the electron transport layer 52 includes doped or undoped inorganic nanocrystals, wherein the undoped inorganic nanocrystals are selected from one or more of ZnO, TiO2, SnO2, Al2O3, CaO, SiO2, Ga2O3, ZrO2, NiO, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP, and MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y.
[0112] In one embodiment, the material of the electron injection layer 51 can be a material known in the art for electron injection layer, for example, it can be selected from but not limited to at least one of LiF, MgP, MgF2, Al2O3, Ga2O3, LiF / Yb, ZnO, Cs2CO3, RbBr, and Rb2CO3.
[0113] In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, I At least one of TZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three stacked layers consisting of an AZO layer, an Ag layer, and an AZO layer.
[0114] The first electrode 10 and the second electrode 20 form a pair of electrodes. In one embodiment, the first electrode 10 is an anode, and the second electrode 20 is a cathode.
[0115] It is understandable that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer.
[0116] It can be understood that the material and thickness of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100 .
[0117] The light emitting device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.
[0118] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device. When the light emitting device 100 is an upright light emitting device, the substrate is combined with a side of the first electrode 10 away from the light emitting layer 30. When the light emitting device 100 is an inverted light emitting device, the substrate is combined with a side of the second electrode 20 away from the light emitting layer 30.
[0119] It is understandable that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer.
[0120] It can be understood that the material and thickness of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100 .
[0121] The present application also provides a method for preparing a light emitting device, see Figure 3 , Figure 3 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:
[0122] Step S21: providing a preset device, wherein the preset device includes a first electrode;
[0123] Step S22: Arranging a hole functional material on the preset device to form a hole functional layer;
[0124] Step S23: forming a stacked light-emitting layer and a second electrode on the hole functional layer to obtain a light-emitting device.
[0125] The light-emitting device prepared in this embodiment is an upright device.
[0126] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S23 specifically includes: forming a stacked light-emitting layer, an electronic functional layer and a second electrode on the hole functional layer to obtain the light-emitting device.
[0127] See also Figure 4 , Figure 4 This is a flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application. The method for preparing a light-emitting device in this embodiment comprises the following steps:
[0128] Step S31: providing a prefabricated device, wherein the prefabricated device comprises a stacked second electrode and a light-emitting layer;
[0129] Step S32: Arranging a hole functional material on the preset device to form a hole functional layer;
[0130] Step S33: forming a stacked first electrode on the hole functional layer to obtain a light-emitting device.
[0131] The light-emitting device prepared in this embodiment is an inverted device.
[0132] In one embodiment, the light-emitting device includes an electronic functional layer, and the step S31 specifically includes: providing a prefabricated device, wherein the prefabricated device includes a stacked second electrode, an electronic functional layer, and a light-emitting layer.
[0133] In the above two embodiments, the hole functional material includes the composite material provided in the present application, or includes a composite material obtained by the method for preparing the composite material provided in the present application. For details, please refer to the relevant description above, which will not be repeated here. In a specific embodiment, the hole functional material is the composite material provided in the present application, or is a composite material obtained by the method for preparing the composite material provided in the present application.
[0134] In one embodiment, in step S22 and step S32, the composite material may be disposed on the prefabricated device by a solution method. Specifically, the solution method may be a spin coating method, a printing method, an inkjet printing method, a doctor blade method, a printing method, a dip-coating method, a soaking method, a spray coating method, a roll coating method, a casting method, a slit coating method, a strip coating method, and the like.
[0135] In a specific embodiment, in step S22 and step S32, the step of arranging the composite material on the preset device to form a hole functional layer includes: arranging a third mixture on the preset device, wherein the third mixture includes the composite material and a third solvent.
[0136] Specifically, the third solvent may include one or more of water and alcohol solvents, and the alcohol solvent may specifically include one or more of methanol, ethanol, isopropanol, n-butanol, and the like.
[0137] Furthermore, the concentration of the composite material in the third mixture may be 10-30 mg / mL, specifically 10-25 mg / mL, 15-25 mg / mL, 15-20 mg / mL, 10-15 mg / mL, 25-30 mg / mL, etc.
[0138] After the third mixture is prepared by the solution method, it is necessary to dry it to remove the third solvent. The drying can be heating drying or vacuum drying. The heating drying temperature can be 60 to 80°C and the time can be 20 to 60 minutes. The vacuum drying pressure is 10 -1 ~10 -2 Pa. Furthermore, the vacuum drying temperature may be room temperature (about 25° C.).
[0139] In this embodiment, the organic hole transport material is an organic macromolecule and has a lower surface energy than nickel oxide. After the third mixture containing the composite material is set on the preset device, during the volatilization and removal of the third solvent in the third mixture, the organic hole transport material with lower surface energy will tend to move away from the preset device, while the nickel oxide tends to move toward the preset device, so that in the formed hole functional layer, in the thickness direction, the concentration of the organic hole transport material increases or decreases, the concentration of the nickel oxide also increases or decreases, and the concentration of the organic hole transport material and the concentration of the nickel oxide change in the opposite trend.
[0140] In other embodiments, the composite material may be disposed on the prefabricated device by other methods known in the art, such as sputtering.
[0141] In each embodiment of the above-mentioned preparation method, the electron transport layer, hole functional layer, light-emitting layer, first electrode, second electrode, etc. can refer to the corresponding description of the light-emitting device 100 in the above text, and will not be repeated here.
[0142] In the light-emitting device provided in the present application, the preparation methods of the first electrode, the second electrode, the light-emitting layer, the hole functional layer, the electron functional layer and other film layers can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.
[0143] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.
[0144] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0145] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0146] Embodiment 1:
[0147] This embodiment provides a method for preparing a composite material and the prepared composite material, wherein the preparation method specifically comprises the following steps:
[0148] Step 1: triethylamine was added to the PEDOT:PSS aqueous solution (5% by mass), and then the solution was irradiated under a 300W Xe lamp (full spectrum) for 1 hour under continuous stirring, during which time it was carried out under the protection of circulating condensed water at 4°C; wherein the mass ratio of triethylamine to PEDOT:PSS was 0.5:5.
[0149] Step 2: Under continuous illumination and stirring, add an aqueous solution of nickel (II) sulfamate to the solution of step 1, wherein the mass ratio of nickel (II) sulfamate to PEDOT:PSS is 40:100; and continue irradiation for 4 hours, during which it is carried out under the protection of circulating condensed water at 4°C. After photodeposition, the above solution is washed three times by precipitation in excess ethyl acetate or acetone to wash away excess copper salt to obtain a composite material.
[0150] Embodiment 2:
[0151] This embodiment is substantially the same as embodiment 1, except that in step 2, the mass ratio of nickel(II) sulfamate to PEDOT:PSS is 45:100.
[0152] Embodiment 3:
[0153] This embodiment is substantially the same as embodiment 1, except that in step 2, the mass ratio of nickel (II) sulfamate to PEDOT:PSS is 55:100.
[0154] Embodiment 4:
[0155] This embodiment is basically the same as embodiment 1, except that in step 2, the mass ratio of nickel(II)sulfamate to PEDOT:PSS is 60:100.
[0156] Embodiment 5:
[0157] This embodiment is substantially the same as embodiment 3, except that in step 2, toluidine-2-sulfonic acid nickel (II) is added instead of aminosulfonic acid nickel (II).
[0158] Embodiment 6:
[0159] This embodiment is substantially the same as embodiment 3, except that in step 2, nickel (II) trifluoromethanesulfonate is added instead of nickel (II) sulfamate.
[0160] Embodiment 7:
[0161] This example is substantially the same as Example 3, except that in step 2, nickel (II) acetylacetonate is added instead of nickel (II) sulfamate, and the irradiation is continued for 7 hours.
[0162] Embodiment 8:
[0163] This embodiment is substantially the same as embodiment 3, except that in step 2, nickel (II) acetylacetonate and nickel (II) trifluoromethanesulfonate (the molar ratio of the two is 1:1) are added instead of nickel (II) sulfamate, and the irradiation is continued for 5 hours.
[0164] Embodiment 9:
[0165] This example is substantially the same as Example 3, except that in step 2, nickel (II) p-toluenesulfonate is added instead of nickel (II) aminosulfonate, and the irradiation is continued for 8 hours.
[0166] Comparative Example 1:
[0167] Step 1: Add an appropriate amount of nickel chloride to 25 ml of deionized water to prepare a nickel chloride solution with a total concentration of 1 M. Weigh an appropriate amount of sodium hydroxide and dissolve it in 5 ml of deionized water to obtain an alkaline solution; add the alkaline solution to the nickel chloride solution at a molar ratio of OH- to nickel ions of 1.7:1 to form a mixed solution with a pH of 13, and then stir at 60°C for 3 hours to obtain a NiOx nanoparticle solution.
[0168] Step 2: Mix the above-mentioned NiOx nanoparticles with the PEDOT:PSS aqueous solution, specifically mixing them according to the mass ratio of NiOx to PEDOT:PSS of 40:100, and stir for 2 hours to obtain a NiOx-PEDOT:PSS mixed material.
[0169] Device Example 1
[0170] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.
[0171] Step 1: Place the ITO glass sheet in a glass dish filled with ethanol solution, and ultrasonicate with acetone, deionized water, and ethanol for 20 minutes respectively, and then blow dry with a nitrogen gun; then place the cleaned ITO glass sheet in oxygen plasma for further cleaning for 10 minutes; continue to use UV-ozone to treat the surface of the ITO substrate for 15 minutes;
[0172] Step 2: Spin-coat the cleaned ITO glass sheets with a solution of the composite material of Example 1 (with a concentration of 30 mg / mL) in air, and anneal at 60° C. for 5 minutes in a glove box after spin coating to obtain a hole functional layer with a thickness of 25 nm;
[0173] Step 3: Spin-coat Cd0.2ZnSe / Cd0.6Zn0.4Se / Cd0.5Zn0.5S / ZnSe / ZnS blue quantum dots on the hole transport layer at a spin-coating speed of 2000 r / min for 30 seconds; after spin-coating, anneal at 60 degrees Celsius in a glove box for 5 minutes to obtain a light-emitting layer with a thickness of 30 nm;
[0174] Step 4: Spin-coat a ZMO ethanol solution (concentration of 30 mg / mL) on the light-emitting layer at a rotation speed of 3000 r / min for 30 seconds, and dry to obtain an electron transport layer with a thickness of 30 nm.
[0175] Step 5: Place the sample prepared in step 4 into a vacuum chamber, evaporate a top silver electrode with a thickness of 100 nm, and encapsulate.
[0176] Device Example 2
[0177] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 2 is used.
[0178] Device Example 3
[0179] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 3 is used.
[0180] Device Example 4
[0181] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 4 is used.
[0182] Device Example 5
[0183] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 5 is used.
[0184] Device Example 6
[0185] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 6 is used.
[0186] Device Example 7
[0187] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 7 is used.
[0188] Device Example 8
[0189] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 8 is used.
[0190] Device Example 9
[0191] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 2, the composite material of embodiment 9 is used.
[0192] Device Comparison Example 1
[0193] This device embodiment is substantially the same as device embodiment 1, with the only difference being that in step 2, the NiOx-PEDOT:PSS mixed material in comparative example 1 is directly used.
[0194] Device Comparison Example 2
[0195] This device embodiment is basically the same as device embodiment 1, except that step 2 is:
[0196] The cleaned ITO glass sheet was spin-coated with PEDOT:PSS in the air at a speed of 3500 r / min and a spin-coating time of 30 seconds; after spin-coating, it was placed in the air for annealing at a temperature of 150°C and an annealing time of 30 minutes to obtain a hole injection layer with a thickness of 25 nm; after annealing, the sheet was quickly transferred to a glove box with a nitrogen atmosphere; TFB (8 mg / mL, chlorobenzene solution) was further spin-coated on the hole injection layer at a speed of 3000 r / min and a spin-coating time of 30 seconds; after spin-coating, it was annealed in the glove box at a temperature of 180°C and an annealing time of 30 minutes to obtain a hole transport layer (with a thickness of 30 nm).
[0197] Test 1:
[0198] In the process of preparing the quantum dot light-emitting diodes in device comparative example 1 and device example 2, after preparing the hole functional layer, an AFM (atomic force microscope) roughness test was performed on the hole functional layer, and the roughness of the hole functional layer was obtained. Figure 5 and Figure 6 ,in, Figure 5 and Figure 6 The AFM images of the hole functional layer in device comparative example 1 and device embodiment 2 respectively correspond to each other.
[0199] Depend on Figure 5 and Figure 6 It can be seen that the arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the hole functional layer in device embodiment 2 are respectively much smaller than the arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the hole injection layer in device comparison example 1, indicating that the hole functional layer formed by the composite material provided in the present application has good film-forming property and surface uniformity. The provided composite material has good film-forming property, which may be due to the fact that the organic anions are connected to the surface of the nickel oxide, which can be combined with a large number of oxygen defects on the surface of the nickel oxide, and effectively reduce the aggregation and regrowth of nickel oxide particles, thereby improving the film-forming property of the composite material.
[0200] Test 2:
[0201] The quantum dot light-emitting diodes of device examples 1-13 and device comparative examples 1-4 were tested for external quantum efficiency EQE and lifetime, and the data are shown in Table 1. Figure 7 , Figure 7EQE-J curves of device examples 1-9 and device comparative examples 1-2. Storage stability monitoring was performed on device examples 3 and 7 and device comparative examples 1 and 2 to monitor the change of external quantum efficiency EQE with storage time. Figure 8 , Figure 8 EQE-storage time diagram of device examples 3 and 7 and device comparative examples 1 and 2.
[0202] (1) The detection method of external quantum efficiency EQE is:
[0203] The ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, expressed in %, is an important parameter for measuring the quality of electroluminescent devices and can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:
[0204]
[0205] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.
[0206] Test conditions: carried out at room temperature, air humidity is 30-60%.
[0207] (2) The test method for life span T95@1000nit is: the time required for the brightness of the device to decrease to a certain proportion of the maximum brightness under constant current or voltage drive. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life span at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:
[0208]
[0209] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of green QLED devices at rated brightness and found that the A value was 1.7.
[0210] Test 3:
[0211] According to the quantum dot light-emitting diodes of device examples 1-13 and device comparison examples 1-4, single hole devices (HOD) are prepared respectively, wherein the preparation method of the single hole device (HOD) is substantially the same as the preparation method of the corresponding complete QLED device, except that the electron transport layer is not prepared, and the obtained single hole device does not include the electron transport layer. The device structure of the single hole device (HOD) is: glass substrate / ITO / hole functional layer / QD light-emitting layer / Ag electrode.
[0212] The hole injection performance test method is:
[0213] A QLED efficiency test system was built by controlling QE PRO and Keithley 2400 through LabView. The system was used to test the current density-voltage curve (JV curve) of the single hole device (HOD). Fig. 9 , Fig. 9 JV curves of single hole devices of device examples 1-9 and comparative examples 1-2.
[0214] Through the current density-voltage curve, the space charge limited current (SCLC) region in the curve is obtained, and then according to the formula J = (9 / 8)ε r ε0μeV 2 / d 3 The hole mobility is calculated and the data is shown in Table 1. Where J represents the current density, with the unit of mAcm -2 ; εr represents the relative dielectric constant, ε0 represents the vacuum dielectric constant; μ e Indicates hole mobility, unit: cm 2 V -1 s -1 ; V represents the driving voltage, unit is V; d represents the film thickness, unit is m.
[0215] Test 4:
[0216] The valence band position of the nickel oxide nanoparticles prepared in Comparative Example 1 was measured. Fig.10 , Fig.10 Figure 2 is the valence band position diagram of nickel oxide (NiOx).
[0217] Method for determining the valence band position: Use nanoparticles to prepare a dry film as a test sample. The film size is about 6*6mm and the thickness is less than 2mm. The Vance band (VB) spectrum is measured using a monochromatic He I light source (21.2eV) and a VG Scienta R4000 analyzer. The sample bias is -5V, and the secondary electron cutoff edge spectrum (SEC) is tested.
[0218] Table 1
[0219]
[0220] As can be seen from Table 1, compared with the device comparative example 1, the hole mobility, external quantum efficiency and life of the device examples 1-9 are significantly improved, indicating that the composite material provided by the present application generates nickel oxide in situ through PEDOT:PSS photocatalysis, and nickel oxide has good bonding with PEDOT:PSS. As the material of the hole functional layer, it is more conducive to the injection of holes, improves the hole mobility of the light-emitting device, thereby improving the carrier injection balance of the light-emitting device, and further improves the external quantum efficiency and life of the device. In addition, the introduction of organic groups can increase the hole concentration and effectively promote hole injection.
[0221] Compared to the device in comparative example 2, which includes a device having two hole functional layers formed by a hole injection layer and a hole transport layer, the single hole functional layer in device example 3 still has better hole mobility, external quantum efficiency and lifetime.
[0222] It can be seen from device embodiments 1-4 that in the preparation process of the composite material, the mass ratio of organic nickel salt to PEDOT:PSS is relatively small (for example, 40:100), which may have a small improvement in the performance of hole injection, and the amount of organic anions is also relatively small, so that the effect on the film formation uniformity and surface smoothness of the hole functional layer is relatively small; while the mass ratio of organic nickel salt to PEDOT:PSS aqueous solution is relatively large (for example, 60:100), so that relatively more nickel oxide is produced, and relatively more organic anions are introduced, which may lead to a decrease in the conductivity of the device, affecting the efficiency of the light-emitting device to a certain extent.
[0223] Depend on Figure 8 It can be seen that the device EQE changes after the complete device is placed in the air for 60 days. The device EQE of the device in device comparative example 2 decreases by 27.64% after being placed for 60 days, while the device embodiments 3 and 7 only decrease by about 5.15%. Compared with device comparative example 2, the degree of damage of the device in device comparative example 1 is also reduced. This may indicate that the organic-inorganic composite material formed by the present application can improve the stability of the device. In addition, during the preparation of the composite material, the inorganic nanoparticle nickel oxide is in-situ dispersed in PEDOT:PSS by photocatalytic technology. The strong interaction between the two makes the film layer more uniform, the leakage current smaller, and the device more stable.
[0224] from Fig.10 It can be seen that the valence band (VB) position of nickel oxide is -5.37 eV, while the valence band position of PEDOT:PSS contained in the composite material is about -5.20 eV, that is, there is a good energy level match between the nickel oxide contained in the composite material and PEDOT:PSS, which can effectively promote the injection of holes.
[0225] The composite materials and preparation methods thereof, light-emitting devices and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A composite material, characterized in that: The invention comprises poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) and nickel oxide, wherein the surface of the nickel oxide is connected with an organic group having negative charge, Wherein, the organic group has one or more of the following structures: Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of -H, -D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 6-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen.
2. The composite material according to claim 1, characterized in that Each occurrence of R1, R2, R3, and R4 is independently selected from -NH2, C1-C10 alkyl, C1-C10 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and aryl having 6-24 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl.
3. The composite material according to claim 2, characterized in that The organic group includes one or more of the following structural formulas:
4. The composite material according to claim 1, characterized in that The average particle size of the nickel oxide is 3 to 10 nm; And / or, the mass ratio of the nickel oxide to the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) is 30-50%.
5. A method for preparing a composite material, characterized in that: include: Providing a first mixture, wherein the first mixture includes poly(3,4-ethylenedioxythiophene):poly(styrenesulfonic acid) and a first solvent, wherein the first solvent contains a hole sacrificial agent; After the first mixture is subjected to a first light treatment, an organic nickel salt is added to the first mixture, and the mixture is subjected to a second light treatment to obtain a composite material; Wherein, the organic nickel salt comprises an organic anion and a nickel ion, and the organic anion comprises one or more of the following structural formulas: Wherein, each occurrence of R1, R2, R3, and R4 is independently selected from one or more of -H, -D, -NH2, C1-C30 alkyl, aryl having 5-30 ring atoms, heteroaryl having 5-30 ring atoms, and C1-C30 alkyl substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, aryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and heteroaryl having 5-30 ring atoms substituted by at least one of -NO2, -CN, -NH2, -OH, -X, and C1-C5 alkyl, and X is halogen.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the organic nickel salt to the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) is (2-3):5; and / or, in the first mixture, the mass percentage concentration of the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) is 0.1 to 20%; and / or, the first solvent includes one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, toluene, and dimethyl sulfoxide; And / or, the hole sacrificial agent includes one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, and lactic acid; And / or, the mass ratio of the hole sacrificial agent to the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) is (0.5-1.5):
5.
7. The preparation method according to any one of claims 5 to 6, characterized in that: The first light treatment adopts full spectrum irradiation; And / or, the first light treatment lasts for 1 to 2 hours; and / or, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30° C.; and / or, during the first light irradiation process, the first mixture is in a stirring state; And / or, the second light treatment uses full spectrum irradiation; And / or, the second light treatment time is 4 to 8 hours; And / or, after adding the organic nickel salt to the first mixture, a second mixture is obtained, and during the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0-30° C. and the second mixture is in a stirring state.
8. A light emitting device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; A light-emitting layer is disposed between the first electrode and the second electrode; A hole functional layer, disposed between the first electrode and the light-emitting layer; Wherein, the material of the hole functional layer includes the composite material as described in any one of claims 1 to 4, or includes the composite material prepared by the preparation method of the composite material as described in any one of claims 5 to 7.
9. The light emitting device according to claim 8, characterized in that: The thickness of the hole functional layer is 15 to 40 nm; And / or, the material of the light-emitting layer is selected from an organic light-emitting material or a quantum dot light-emitting material; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, and the The II-VI compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, Cd ZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, Hg At least one of ZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb , at least one of GaPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - ,I - At least one of; And / or, the first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, IT At least one of ZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; And / or, the light-emitting device also includes an electronic functional layer, which is arranged between the second electrode and the light-emitting layer, and the material of the electronic functional layer includes doped or undoped inorganic nanocrystals; wherein the undoped inorganic nanocrystals are selected from one or more of ZnO, TiO2, SnO2, Al2O3, CaO, SiO2, Ga2O3, ZrO2, ZnS, ZnSe, CdS, InP, GaP, BaTiO3, Cs2CO3, Rb2CO3, RbBr, LiF, LiF / Yb, MgP, MgF2; the doped inorganic nanocrystals include the undoped inorganic nanocrystals and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y.
10. A display device, characterized in that: The light emitting device comprises the light emitting device as claimed in any one of claims 8 to 9.